2014
DOI: 10.1002/ccd.25779
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation using the left transcarotid approach in patients with previous ipsilateral carotid endarterectomy

Abstract: TAVI through a left transcarotid approach in patients previously operated on for ipsilateral CEA is feasible and safe. The presence of a previous ipsilateral CEA represents no more a limitation to the utilization of this promising access route. At short-term follow-up, mortality and major complications rates are low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…More recently, Azmoun et al reported no cerebrovascular events or access site complications in a series of 19 patients undergoing TAVI of both self-expanding and balloon-expandable valves via transcarotid access under local anaesthesia [15]. To date, further available data seem to confirm the safety and feasibility of this access site [16,17]. Furthermore, a first report of valve-in-valve implantation for degenerated stentless aortic root conduits with severe regurgitation via transcarotid access has described three uneventful cases [18].…”
Section: Discussionmentioning
confidence: 91%
“…More recently, Azmoun et al reported no cerebrovascular events or access site complications in a series of 19 patients undergoing TAVI of both self-expanding and balloon-expandable valves via transcarotid access under local anaesthesia [15]. To date, further available data seem to confirm the safety and feasibility of this access site [16,17]. Furthermore, a first report of valve-in-valve implantation for degenerated stentless aortic root conduits with severe regurgitation via transcarotid access has described three uneventful cases [18].…”
Section: Discussionmentioning
confidence: 91%
“…20 of those reported) were found to have mild paravalvular regurgitation (13,15,19,22,23), while three patients (4.1% of those reported) were found to have moderate paravalvular regurgitation (8,15,24); there was no incidence of severe paravalvular regurgitation.…”
Section: Accepted M Manuscriptmentioning
confidence: 85%
“…Two transient ischaemic attacks were reported (10,18). 10 patients required a transfusion of at least 2 units of packed red cells (8,15,19). One patient required new dialysis for acute kidney injury (19).…”
Section: Other Perioperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations